2022
DOI: 10.1111/jfb.15242
|View full text |Cite
|
Sign up to set email alerts
|

Global trends, biases and gaps in the scientific literature about freshwater fish eggs and larvae

Abstract: Syntheses of knowledge are important to reveal trends, biases and gaps in the scientific literature, indicating main data shortfalls and research needs. In this regard, the authors conducted a broad systematic review on the literature about freshwater fish eggs and larvae to investigate (a) temporal trends in the global scientific production, (b) the scope and habitat types, (c) the spatial distribution of studies, (d) the fish species contemplated and their respective conservation status and (e) the factors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…This general model has explained the reproductive success and recruitment in different Neotropical basins that contain floodplains (Agostinho et al ., 2004; Jiménez‐Segura et al ., 2010; Rosa et al ., 2018). Nonetheless, important river basins in the region still lack an investigation into the patterns of reproduction of fish species, especially with regard to the ecological study of eggs and larvae (Carnicer et al ., 2023; Reynalte‐Tataje et al ., 2020). This is the case for river basins in savanna ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…This general model has explained the reproductive success and recruitment in different Neotropical basins that contain floodplains (Agostinho et al ., 2004; Jiménez‐Segura et al ., 2010; Rosa et al ., 2018). Nonetheless, important river basins in the region still lack an investigation into the patterns of reproduction of fish species, especially with regard to the ecological study of eggs and larvae (Carnicer et al ., 2023; Reynalte‐Tataje et al ., 2020). This is the case for river basins in savanna ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced spawning success alters fish recruitment and thus can lead to population declines and even ecosystem collapse (Wright & Trippel, 2009). Unfortunately, knowledge about how environmental variation affects fish spawning strategies and success is often quite limited (Carnicer et al., 2023). Spawning requirements and success can vary not only between different species but also among geographically separated populations within the same species (Teletchea et al., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In this issue, Carnicer et al (2022) apply this thinking to the field of freshwater fish eggs and larvae by conducting a scientometric review on the scientific literature, analysing 654 studies published between 1950 and 2020, to identify global trends, biases and literature gaps. The results from their analysis are both illuminating and thought provoking and provide insights that are vital to improving the scientific literature.…”
mentioning
confidence: 99%
“…It was found that most of the studies investigated basic questions on the biology and ecology of fish eggs and larvae such as environmental conditions, spawning areas and recruitment. Carnicer et al (2022) highlight that many of these studies had been published in low‐impact journals or remained in unpublished grey literature, with minimal impact, which could demonstrate the need for more novel hypothesis testing and experimental manipulation. Although basic research is an important first steppingstone, especially for the many data deficient fish species found globally.…”
mentioning
confidence: 99%
See 1 more Smart Citation